Pristane plus v-abl/myc induced lymphoma and plasmacytoma development in STS/A mice - Sakulratchata, Ruedee; Kriangkrai, Rungarun; Mai, Sabine (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 1 (2014): January-April 2014, 2014)
The STS/A (STS) mouse is a highly resistant strain for radiation-induced hematopoietic and mammary gland neoplasms while BALB/cHeA mouse is susceptible. The BALB/c mouse strain is also sensitive to peritoneal plasmacytoma (PCT) induction by a variety of agents, including plastic implants, paraffin oils, pristane and pristane plus v-abl/myc, with different latency periods, incidences and effectiveness.         The objective of this study was to investigate the susceptibility of the STS mouse to pristane plus v-abl/myc induced plasmacytomagenesis.         Materials and methods: Ten mice from a control group were intraperitoneally injected with pristane only and the other ten mice were injected with pristane followed by v-abl/myc. All mice were investigated routinely for ascitis and tumor formation up to 100 days. Histologic slides were prepared from harvested tumor samples as well as CD138 immunofluorescence staining for plasma cells detection.         Results: Four of ten mice in pristane plus v-abl/myc group developed ascites and showed evidence of lymphoid malignancies. Three of the ten mice had mixed tumors (lymphoma and PCT) and one of ten had lymphoma. None of the control STS mice developed a tumor. The average latency period of tumor development in STS mice was 90 days which was longer than pristane plus v-abl/myc plasmacytomagenesis in BALB/c and congenics. The relative risk of tumor resistance of a control group compared to the test group was 1.67 (95% confidence interval (CI): 1.005-2.765).         Conclusion: The STS mice were not completely tolerate to pristane plus v-abl/myc plasmacytoma induction but an average latency period of tumor formation was longer than the BALB/c and congenics mouse strain. This extended period indicated some resistances in the STS genetic background. Keywords: lymphoma, plasmacytoma, mouse tumor induction, mouse chromosome 11, v-abl/myc
Keywords: lymphoma, plasmacytoma, mouse tumor induction, mouse chromosome 11, v-abl/myc